Police Ambassadors: Student‐Police Interactions in School and Legal Socialization. Issue 2 (8th May 2020) - Kupchik, Aaron; Curran, F. Chris; Fisher, Benjamin W.; Viano, Samantha L.
Abstract : The recent influx of police officers into US public schools has reshaped the context and frequency of children's interactions with police. Yet we know little about how the presence of these officers in schools impacts the legal socialization of students, and whether youth of color might be affected or socialized in different ways than white youth. In this study, we analyze data from interviews with school police officers as well as focus group data from school staff, parents, and students that shed light on how school police interact with youth. In particular, school police officers discussed their desire to build relationships with students that instill trust in police among students. Officers discussed their efforts to teach students that police should be trusted and relied on, and that negative views of policing and involvement with the justice system are the result of a negative news media and individual citizens' criminality, respectively. Importantly, officers discussed how they devote particular attention to imparting these lessons on youth of color and others who may see police in a negative light. We consider how these outreach efforts, what we call acting as police ambassadors, might have different impacts on youth of color compared to white youth, given existing racial disparities in interactions with police.